Perubahan dan Inovasi Kurikulum Pendidikan di Berbagai Negara - Firli Fangestu, Indra Wahyuni; Siti Marpuah; Bahrissalim; Fauzan (Southeast Asian Journal of Islamic Education Management, 2025)
Changes and innovations in the educational curriculum are very important elements in answering the challenges of the times that continue to develop. The curriculum innovation process carried out in various countries, including Indonesia, reflects efforts to accommodate new needs in the world of education. This article examines changes and innovations in the educational curriculum with a focus on key findings obtained from research in Indonesia and Indonesia and other countries such as; Malaysia, Finland, Singapore, Canada, Australia, China, and the United States through the library research method, this study analyzed various previous studies, including journals, books, and related articles. The purpose of this study is to examine changes and innovations in the educational curriculum with a focus on the factors driving these changes and the challenges faced in their implementation. The results of the study show that curriculum changes and innovations are triggered by several key factors: 1) technological advances that affect learning methods, 2) job market demands and economic changes that demand new skills, and 3) socio-cultural changes that encourage the adjustment of teaching materials. Although various countries have innovated curricula according to local needs, significant challenges remain, namely: 1) teachers' readiness to implement the new curriculum, 2) the availability of resources that support the learning process, 3) resistance to existing changes, and 4) the lack of a comprehensive evaluation of the effectiveness of previous curricula. These findings highlight the importance of collaborative strategies to address these challenges to support the success of curriculum innovation.